Character Education during the Covid-19 Pandemic in Elementary School - Akhwani Akhwani; M. Afwan Romdloni (Universitas Pendidikan Indonesia (UPI), 2021)
The Covid-19 pandemic has had a shocking effect in the education sector. Online-based learning is a solution during a pandemic. In a COVID-19 pandemic situation character education should not be ignored, especially at the elementary school level. It is because character education is an integral part of education, especially basic education. Elementary school students really need character education for their development needs. Preparing a good generation is the same as instilling prosperity for the future. This study aims to identify the implementation of character education in elementary schools in terms of learning tools; teaching and learning activities; teaching methods; and evaluation. The research method used was descriptive exploratory research. Data was obtained from a survey of elementary school teachers through open and closed questionnaires. The results showed that: the learning tools were designed by adjusting the simplified basic competencies without leaving the Core Competencies (KI) 1 and 2. Learning methods carried out were online, offline, and blended with attention to affective aspects. Learning is designed to instill the values of learning discipline, responsibility in completing tasks, instilling healthy life patterns, honesty, and religious attitudes. Evaluation was done through questionnaires and communication with parents, questionnaires, and rewards. Teachers need to creatively design learning while still considering the character education during the Covid-19 pandemic. Character education during a pandemic will provide a character-based life pattern from an early age anywhere and under any conditions.